Kesan Aktiviti Regangan Rossiter System Terhadap Pemulihan Kesengalan Serat Cetusan Lewat - Thung, Jin Seng (2009)

(untitled)
Practically every one involved in sports practice would experience Delayed-Onset-Muscle-Soreness (DOMS). Several modalities have been utilized to reduce DOMS such as anti-oxygen vitamin and drugs intake, ice bath, spa and pre and post exercise stretching. However, not all recovery modalities have been scientifically proven to aid DOMS recovery. This study was carried out to examine the effectiveness of several physical modalities for treating DOMS after training. The purpose of this study was to examine the effectiveness of Rossiter System® stretching and light aerobic activities for recovering from DOMS. Thirty six healthy male subjects volunteered to participate in this study and were randomly divided into three groups; a control group (KK), the Rossiter group (KR) and the aerobic group (KA). DOMS was induced through the completion of five sets of eccentric bicep curls with dumbbells weighing 13kg, 10kg, 7kg, 5kg and 3kg. Subjects were required to maintain five seconds throughout the descending phase of the bicep curls untill failure for each set. The KK group rested right after the bicep curls. The KR group performed Rossiter System® stretching while the KA group performed 50 repetitions of bicep curls without dumbbells at their own pace immediately after the exercise. Data such as plasma creatine kinase (CK), biceps’ circumference and perceptive soreness scales were obtained before, immediately right after, 24, 48, 72, 120 and 168 hours after DOMS was induced. Subjects were instructed to fully restrict supplement and drug intake and not be involved in aggressive physical activity and self massage during the period of the study. Three subjects were dropped from this study due to non-adherence to the criteria of the study. Results of the data analysis indicated that they were no significant different between KR and KA against KK for all testing sessions. Data also indicated that they were no significance difference between KR and KA against all three dependant variables. The study concluded that a single session of either physical modality immediately after the DOMS was induced is not effective. However, there is a trend suggesting that KR experienced less DOMS compared with KA, and KA experienced less DOMS compared with KK, after the first 24 hours. Further studies should focus on multiple bouts of treatment after inducing DOMS.